All Days 2014
DOI: 10.2118/168012-ms
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Casing Centralization on Cement Sheath Integrity During Thermal Cycling

Abstract: The objective of primary cementing is to protect the casing and to ensure zonal isolation. It can be difficult to obtain a good cement job along the full length of a well, and casing centralization is one of the main factors that influence this. Even if the dependence of cement placement on casing centralization is well-known, little information is available on how the degree of casing centralization affects the well during its production phase. Well temperatures cycle up and down as a part of normal productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 8 publications
3
24
0
Order By: Relevance
“…Similar trends, displaying that both pressure and temperature variations aggravate the casing/cement bond, were observed by Boukhelifa et al (2004) and Bois et al (2012). Detailed experimental studies of annular-cement debonding and cracking were also recently performed by Albawi et al (2014) andDe Andrade et al (2014). Both these studies show that only a few thermal cycles in the range of -20 C to 120 C cause cement debonding and cracking that are visible in computed-tomography images.…”
Section: Introductionsupporting
confidence: 67%
“…Similar trends, displaying that both pressure and temperature variations aggravate the casing/cement bond, were observed by Boukhelifa et al (2004) and Bois et al (2012). Detailed experimental studies of annular-cement debonding and cracking were also recently performed by Albawi et al (2014) andDe Andrade et al (2014). Both these studies show that only a few thermal cycles in the range of -20 C to 120 C cause cement debonding and cracking that are visible in computed-tomography images.…”
Section: Introductionsupporting
confidence: 67%
“…Several recent studies report on application of thermal loads to downscaled wellbore section models (Albawi et al 2014;De Andrade et al 2014). Albawi et al (2014) developed an experimental setup for thermal cycling with monitoring of acoustic emission and temperature, and tested it in a set temperature interval of Ϫ20 to 120°C to simulate conditions in an Arctic well.…”
Section: Introductionmentioning
confidence: 99%
“…Some increase in void/crack volumes was observed for both specimens after the thermal cycling, especially for the stand-off specimen. The temperature ranges used in these studies (Albawi et al 2014;De Andrade et al 2014) were limited to temperatures above 0°C. These studies revealed the need for cold thermal cycling (below 0°C).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar trends, displaying that both pressure and temperature variations aggravate the casing-cement bond, have been observed by Boukhelifa et al (2005) and Bois et al (2012). Detailed experimental studies of annular cement debonding and cracking have also recently been performed by Albawi et al (2014) andDe Andrade et al (2014). Both these studies show that only a few thermal cycles in the range Ϫ20°C to 120°C cause cement debonding and cracking that is visible in computed tomography (CT) images.…”
Section: Introductionmentioning
confidence: 99%